Antioxidant and angiotensin I-converting enzyme (ACE) inhibitory peptides of rainbow trout (Oncorhynchus mykiss) viscera hydrolysates subjected to simulated gastrointestinal digestion and intestinal absorption (2022)
ABSTRACT: The objective of this work was to evaluate in vitro bioaccessibility, intestinal absorption, antioxidant and angiotensin I-converting enzyme (ACE) inhibitory activities of peptides from rainbow trout viscera hydrolysate (H). Rainbow trout Viscera (V) was hydrolyzed by Alcalase® 2.4L and a degree of hydrolysis (DH) of 44.8 ± 2.5% was achieved. Viscera and its hydrolysate were subjected to simulated gastrointestinal digestion (SGID) and intestinal absorption across Caco-2/TC7 cell monolayers. After the hydrolysis with Alcalase® 2.4L and the SGID of V, the species between 60.6 kDa and 13.0 kDa were decreased, causing an increase in species less than 6.51 kDa. The SGID of H did not modify the oxygen radical absorbance capacity (ORAC) or ACE inhibitory values but caused a significant decrease in the hydroxyl radical antioxidant capacity (HORAC) (30.2%). It also produced an increase in ABTS radical cation (ABTS assay) scavenging activity and ferric reducing antioxidant power (FRAP) (9.46% and 20.2%, respectively). Bioactive peptides in H were stable after SGID and they were partially able to cross Caco-2/TC7 cell monolayer, which demonstrates their possible intestinal absorption and their potential to act inside the organism.